The acceptance of environmental friendly practices among smallholders in oil palm / Nurfidatul Denan - Denan, Nurfidatul (Faculty of Plantation and Agrotechnology, 2018)
The environmental friendly practices is used to reduce or minimize the environmental pollutions and deforestation. The purpose of study is to assist acceptance level about environmental friendly practices in proper management. Besides, to evaluate the most factors (Knowledge, environment safety, good farm practices and ecosystem) between the acceptance levels environmental friendly practices among smallholders. The survey method is used for data collection and was distributed to 52 respondents that consists of smallholder in Gersik sub-division of Tangkak, Johor. The results were interpreted by hypothesis testing, descriptive analysis, Pearson correlation and Regression analysis by using Statistical Package for the Social Science (SPSS) version 22. The reliability test was checked using the Cronbach‟s Alpha and the value obtained was 0.808 that the survey can be proceed by distributing the questionnaire to the targeted respondents. After that, Pearson correlation analysis was carried out to determine the relationship between independent variables and dependent variable. There were very high relationship between all independent which with dependent variables, r = 0.805, 0.862, 0.887and 0.593 respectively. Meanwhile, the significance p value were 0.000 which less than 0.05, so null hypothesis (Ho) was rejected. Thus, it can be concluded that there positive significant relationship between independence variable and dependent variable. For result regression analysis, stated that the most influence variable toward the acceptance level environmental friendly practices is environment safety with the β= 0.593. From the model analysis, there are about 80.4% dependent variable was explained independent variable and 19.6% was explained by another factors. Conclusion, environmental friendly practices is one of suitable method to manage the farm in good management likes good drainage system, no open burning, correcting timing for harvesting and pruning and others activities. This is due to the concept of environment is nature and do not harmful to the human health. Not only that, it may increases the yield and productivity of the oil palm .Thus, the smallholders must apply the concept of environmental friendly practices in their plantation management.